Faktor-Faktor yang Mempengaruhi Produk Domestik Bruto di Asia Tenggara - Fajari Himannudin; Marselina Marselina; Arivina Ratih; Asih Murwiati (Journal of Regional Economics Indonesia, 2022)
The indicator of economic growth in a country is the Gross Domestic Product. This study aims to analyze the influence of economic factors and human development on Gross Domestic Product in Southeast Asia during the period 2017-2019. This study uses panel data analysis with descriptive and quantitative methods. The results of the study found that partially the variables of government expenditure, labor force, and human development index have a positive and significant effect on Gross Domestic Product in Southeast Asia, while foreign investment do not have a significant effect on Gross Domestic Product in Southeast Asia. Simultaneously, the variables of government expenditure, foreign investment, labor force, and the human development index have a positive and significant effect on the Gross Domestic Product in Southeast Asia.